Effect of telecare on use of health and social care services: findings from the Whole Systems Demonstrator cluster randomised trial. - Steventon, A; Bardsley, M; Billings, J; Dixon, J; Doll, H; Beynon, M; Hirani, S; Cartwright, M; Rixon, L; Knapp, M; Henderson, C; Rogers, A; et al. (2013)
OBJECTIVE: to assess the impact of telecare on the use of social and health care. Part of the evaluation of the Whole Systems Demonstrator trial. PARTICIPANTS AND SETTING: a total of 2,600 people with social care needs were recruited from 217 general practices in three areas in England. DESIGN: a cluster randomised trial comparing telecare with usual care, general practice being the unit of randomisation. Participants were followed up for 12 months and analyses were conducted as intention-to-treat. DATA SOURCES: trial data were linked at the person level to administrative data sets on care funded at least in part by local authorities or the National Health Service. MAIN OUTCOME MEASURES: the proportion of people admitted to hospital within 12 months. Secondary endpoints included mortality, rates of secondary care use (seven different metrics), contacts with general practitioners and practice nurses, proportion of people admitted to permanent residential or nursing care, weeks in domiciliary social care and notional costs. RESULTS: 46.8% of intervention participants were admitted to hospital, compared with 49.2% of controls. Unadjusted differences were not statistically significant (odds ratio: 0.90, 95% CI: 0.75-1.07, P = 0.211). They reached statistical significance after adjusting for baseline covariates, but this was not replicated when adjusting for the predictive risk score. Secondary metrics including impacts on social care use were not statistically significant. CONCLUSIONS: telecare as implemented in the Whole Systems Demonstrator trial did not lead to significant reductions in service use, at least in terms of results assessed over 12 months.